Inactivation of kallikrein in human plasma. - van der Graaf, F (1983)
Human plasma kallikrein is inactivated by plasma protease inhibitors. This study was designed to determine the nature of these protease inhibitors and to assess their relative importance in the inactivation of kallikrein. Therefore, the kinetics of kallikrein inactivation and the formation of kallikrein inhibitor complexes were studied in normal plasma and in plasma depleted of either alpha 2-macroglobulin (alpha 2M), C1 inhibitor, or antithrombin (AT III). Prekallikrein was activated by incubation of plasma with dextran sulfate at 4 degrees C. After maximal activation, kallikrein was inactivated at 37 degrees C. Inhibition of kallikrein amidolytic activity in AT III-deficient plasma closely paralleled the inactivation rate of kallikrein in normal plasma. The inactivation rate of kallikrein in alpha 2M-deficient plasma was slightly decreased compared with normal plasma, but in contrast to normal, C1 inhibitor-deficient, and AT III-deficient plasma, no kallikrein amidolytic activity remained after inactivation that was resistant to inhibition by soybean trypsin inhibitor. Suppression of kallikrein activity in C1 inhibitor-deficient plasma was markedly decreased, and this was even more pronounced in plasma deficient in both C1 inhibitor and alpha 2M. The pseudo first-order rate constants for kallikrein inactivation in normal, AT III-deficient, alpha 2M-deficient, C1 inhibitor-deficient plasma, and plasma deficient in both alpha 2M and C1 inhibitor, were 0.68, 0.60, 0.43, 0.07, and 0.016 min-1, respectively. Sodium dodecyl sulfate gradient polyacrylamide slab gel electrophoresis showed that during inactivation of kallikrein in plasma, high-Mr complexes were formed with Mr at 400,000-1,000,000, 185,000, and 125,000-135,000, which were identified as complexes of 125I-kallikrein with alpha 2M, C1 inhibitor, and AT III, respectively. In addition, the presence of an unidentified kallikrein-inhibitor complex was observed in AT III-deficient plasma. 52% of the 125I-kallikrein was associated with C1-inhibitor, 35% with alpha 2M, and 13% with AT III and another protease inhibitor. A similar distribution of 125I-kallikrein was observed when the 125I-kallikrein inhibitor complexes were removed from plasma by immunoadsorption with insolubilized anti-C1 inhibitor, anti-alpha 2M, or anti-AT III antibodies. These results suggest that only covalent complexes are formed between kallikrein and its inhibitors in plasma. As a function of time, 125I-kallikrein formed complexes with C1 inhibitor at a higher rate than with alpha 2M. No difference was observed between the inactivation rate of kallikrein in high-Mr kininogen-deficient plasma and that in high-Mr kininogen-deficient plasma reconstituted with high-Mr kininogen; this suggests that high-Mr kininogen does not protect kallikrein from inactivation in the plasma milieu. These results have quantitatively demonstrated the major roles of C1 inhibitor and alpha 2M in the inactivation of kallikrein in plasma.